Shevchenko studies of Yurii Lavrinenko (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article is devoted to unknown page of J. Lawrynenko’s scientific legacy – Shevchenko’s theme. Lawrynenko examined the category of love and kordocentryzm as a creative, ethic, structural-semiotics center of poetry and all life of T. Shevchenko.
Keywords: T. Shevchenko; P. Kulish; M. Drahomanov; I. Franko; cordocentrysm